Respuesta :
Answer:
3
Step-by-step explanation:
Note the general factorisation of a difference of 2 squares is
a² - b² = (a + b)(a + b)
Given
(- 5x - 3)(- 5x + ?)
Then ? = 3 so that the complete factors are
(- 5x - 3)(- 5x + 3)
The term which completes the product so that it is difference of two squares is 3
Difference of two squares
a² – b² = (a + b)(a – b)
How to determine the missing term
Let the missing term be b
- (−5x − 3)(−5x +
- Value of b =?
Since the expression is difference of two squares, it means the bracket must contain the same entity but with a different sign.
a² – b² = (a + b)(a – b)
(−5x − 3)(−5x + b) = (a + b)(a – b)
Comparing the above, we can see that b = 3
Therefore, the missing term is 3 as shown below:
(−5x − 3)(−5x + b) = (−5x − 3)(−5x + 3)
Learn more about difference of two squares:
https://brainly.com/question/914765